CORINTH’S TRADE WITH THE ADRIATIC - Slane, Kathleen (Rei Cretariae Romanae Fautorum Acta, 2024)
Corinth’s location at the head of the Gulf of Corinth ensured its importance in trade from the Classical period until the fall of Constantinople to the Turks in 1453. It provided a relatively tranquil sea route between the Aegean and Italy interrupted only by the short trip across the Isthmus and was a preferred alternative to the longer, storm-tossed sea-route around Cape Malea or the land-route offered by the Via Egnatia. Corinthian colonies on Corfu, at Apollonia and Epidamnos along the eastern coast of the Adriatic and in Sicily (founded in the 7th and 6th cent. BC) show the Corinthians’ original areas of interest in the West.